High levels of genetic structure and striking phenotypic variability in a sexually dimorphic suckermouth catfish from the African Highveld. (12th September 2015) - Morris, Jake; Ford, Antonia G. P.; Ali, Jarome R.; Peart, Claire R.; Bills, Roger; Day, Julia J.
Abstract : Uncovering biological diversity to more accurately understand diversity patterns, and ultimately the processes driving diversification, is important not only from an evolutionary perspective but also a conservation perspective. This is particularly pertinent in Africa's rivers in which overall diversity, as well as how it arose, is poorly understood in comparison with lacustrine environments. Here we investigate population divergence in the sexually dimorphic suckermouth catfish species Chiloglanis anoterus (Crass, 1960) from the African Highveld, in which we observe striking variability in exaggerated male caudal fins across its range. As this trait is likely to be indirect evidence for sexual selection by female choice, a mechanism that has been shown to increase species diversity in different taxa, we used an integrated approach to test if current diversity in this species is underestimated. Results based on phylogenetic inference, population genetics and geometric morphometrics indicate that the recognized species C. anoterus represents five distinct lineages that may be considered confirmed candidate species. We suggest that diversification in these highland catfish has been facilitated through geographical isolation in upper river catchments, and that sexual selection through female choice has probably driven variation in male caudal fin morphology. In contrast to the relatively large range size of the currently recognized species ( C. anoterus ), our findings highlight highly restricted ranges of the lineages identified here, indicating that these highland habitats may harbour higher levels of endemic diversity than previously thought.